Numerical Investigation of Submarine Spreading Landslide Failures - Chen, Qian; Shen, Jiayi; Ku, Meng; Wang, Lizhong (Geotechnical and geological engineering, 2025)
Submarine spreading landslides are geological disasters which frequently occur in sensitive clay slopes and have the ability to destroy underwater offshore engineering infrastructure and trigger tsunamis. This study investigates the failure topography of submarine spreading landslides using the Coupled Eulerian–Lagrangian (CEL) approach within ABAQUS. It is found that the water flowing into gaps between Δ-shaped horsts and ∇-shaped grabens plays two crucial roles in forming a specific form of topography of submarine spreading landslides. On the one hand, water pressure acting on the back of the horst makes the horst move forward in a stable Δ-shaped form. By contrast, water pressure acting on the front of the graben leads to the unstable ∇-shaped graben flipping into a stable Δ-shaped form, resulting in the blocks in the deposit of submarine spreading landslides almost appearing in the Δ-shaped horst. On the other hand, the interaction between sliding masses and vortices generated during the landslides erodes the surface of the sliding mass during spreading failure, causing a large amount of softened and remolded soil which submerges the horst group and forms the almost horizontal surface of the soil deposit after submarine spreading landslides. These two interactions between the water and the sliding mass can well explain why the deposit of submarine spreading landslides consists of Δ-shaped horst groups surrounded by a large amount of remolded soil below the horizontal surface. Such topography is quite different from typical onshore spreading landslides having both Δ-shaped horsts and ∇-shaped grabens.